Analysis of instruments for screening of childhood development - Sigolo, Ana Regina Lucato; Aiello, Ana Lúcia Rossito (Paidéia (Ribeirão Preto), 2011)
The literature shows the importance of early identification of child development delays and difficulty in choosing assessment instruments. The objectives of this study were to compare the Denver II and RDB with a scale of reference (EEDP) concerning children identification with delay of development; to verify difference in the results considering gender of the participants and to investigate results convergence of the scales. Participants were 24 babies with ages ranging from five to 11 months, both sex, attending to local nurseries. The instruments were administered individually and sequentially pre-defined. Statistical analysis revealed that the scale RDB and the Denver II may not be considered similar to the scale EEDP. Considering sex, there was no significant difference. There was no convergence of faulty items in the areas. Therefore, important to be careful on the choice of instruments for screening and obtaining information from different sources on child development.